Diagnosis and Surgical Management of Uterine Cancer: A Comprehensive Systematic Review of Minimally Invasive Techniques, Molecular Staging, and Oncological Outcomes - Ramos Silalahi; Silvia Witarsih (International Medical Journal Corp. Ltd, 2025)
Introduction Uterine cancer, overwhelmingly represented by endometrial carcinoma (EC), is the most frequently diagnosed gynecologic malignancy in developed nations, with incidence rates steadily rising. Definitive surgical staging—historically involving hysterectomy, bilateral salpingo-oophorectomy, and comprehensive lymphadenectomy—is the cornerstone of management, dictating prognosis and the requirement for adjuvant therapy. This review systematically synthesizes high-level evidence on comparative diagnostic accuracy, the oncological safety of minimally invasive surgery (MIS) versus open surgery (OS), and the non-inferiority of Sentinel Lymph Node Biopsy (SLNB) in the context of emerging molecular risk stratification frameworks, notably the 2023 International Federation of Gynecology and Obstetrics (FIGO) staging system. Methods A rigorous systematic search was executed across major medical literature databases (PubMed, Google Scholar, Semantic Scholar, Springer, Wiley Online Library) for comparative studies, systematic reviews, and meta-analyses published since 2017. Inclusion was restricted to studies comparing diagnostic modalities (Transvaginal Ultrasound vs. Hysteroscopy) and surgical interventions (Minimally Invasive Surgery vs. Open Surgery; SLNB vs. comprehensive Lymphadenectomy) in EC patients. Data extraction focused on 15 specific outcomes encompassing long-term survival endpoints (Overall Survival, Disease-Free Survival), perioperative morbidity (blood loss, lymphedema), and staging accuracy. Given the observational nature of most surgical comparisons, the Risk of Bias in Non-randomized Studies – of Interventions (ROBINS-I) tool was employed for quality assessment (Cochrane Methods Bias, 2024). Results The synthesis incorporated evidence from 16 high-quality publications, integrating data from meta-analyses pooling over 10,000 patients. Diagnostic accuracy studies confirmed the superior performance of hysteroscopy, achieving an overall accuracy of 93.3% versus 83.5% for TVUS (Huang et al., 2023). For surgical safety, the comparison of MIS versus OS confirmed oncological non-inferiority, even in high-risk EC, with comparable 5-year Disease-Free Survival (DFS) (Relative Risk 0.93, 95% CI 0.82–1.05) and Overall Survival (OS) (RR 0.92, 95% CI 0.77–1.11) (Mariani et al., 2023). Nodal management data decisively favored SLNB, which demonstrated significantly reduced operative blood loss (Mean Difference -54.40) and minimized the long-term risk of debilitating lymphedema (RR 0.25) (Chen et al., 2020; SGO/Mayo Clinic, 2021). Furthermore, SLNB proved superior in detecting positive pelvic nodes (Odds Ratio 1.35) due to mandatory ultra-staging protocols (Toro et al., 2019). Discussion The collective, high-level evidence mandates a unified standard of care for EC: an approach that is minimally invasive, highly selective in nodal staging via SLNB, and precisely guided by molecular risk stratification (FIGO 2023). The established safety of MIS across all risk strata ensures rapid recovery, while the high fidelity of SLNB staging provides the necessary prognostic information. The integration of molecular markers (e.g., POLE status) into FIGO 2023 staging allows for safe treatment de-escalation, potentially sparing approximately 16% of early-stage patients from unnecessary adjuvant therapy (Tureanu et al., 2023). Conclusion Minimally Invasive Surgery and Sentinel Lymph Node Biopsy are decisively endorsed as the standard surgical approach for EC, providing equivalent oncological outcomes to traditional methods while significantly improving surgical safety and quality of life metrics. Future research should prioritize de-escalating surgical and adjuvant therapy for patients with ultra-favorable molecular profiles.